Digitalization of Pipang Product Marketing for Increasing SME Sales - Ilman, I.; Ramlan , Pratiwi; Sofyan , Wahyudi; Razak , Muhammad Rais Rahmat; Hardianti , H. (Manunggal Halim Jaya, 2025)
This study focuses on pipe marketing to increase SME sales in Puncak Harapan Village, which lacks extensive marketing strategies and brands with significant selling value. It aims to leverage the potential of digital technology to expand opportunities for the growth and success of SME businesses in the current digital era. This study aims to analyze the appropriate digitalization of pipe marketing to enhance SME sales in Puncak Harapan Village, Enrekang Regency. The qualitative research method uses data analysis techniques with NVivo 12 Plus. Researchers will conduct in-depth interviews with informants to identify the most effective digital strategies for pipeline marketing. This study concludes that digitalizing product marketing in Puncak Harapan Village, Enrekang Regency, through platforms such as Shopee and Facebook, is crucial in increasing SME sales. Shopee is more effective by employing aggressive marketing tactics, while Facebook focuses on in-depth situational analysis to tailor strategies to consumer preferences. Effective marketing tactics and strategies on digital platforms significantly influence the success of SME product marketing. However, proper implementation and control are also essential to ensure the effectiveness of these strategies, particularly in response to market dynamics and consumer feedback.